1996
DOI: 10.1002/(sici)1098-240x(199608)19:4<311::aid-nur5>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Family climate and parent-child relationships: Recollections from a nonclinical sample of adult children of alcoholic fathers

Abstract: Past family climate and past parent-child relationships of a nonclinical sample of young adult children of alcoholic fathers (n = 87) were compared to a sociodemographically similar sample of young adults with nonalcoholic parents (n = 106). Self-reports indicated that, compared to respondents from nonalcoholic families, respondents with alcoholic fathers described a more negative family climate with higher levels of conflict and lower levels of cohesion and expressiveness. Adult children of alcoholics describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Bowlby (1969Bowlby ( , 1980 suggested that interactions with caregivers contribute to the development of internal working models about the world. During periods of active abuse, alcohol-abusing parents may be inconsistent, insensitive, angry, and rejecting (MacPherson et al, 2001;Tweed & Ruff, 1996). The inconsistent behavior displayed by some alcohol-abusing parents may convey to their children that they are unworthy.…”
Section: Discussionmentioning
confidence: 99%
“…Bowlby (1969Bowlby ( , 1980 suggested that interactions with caregivers contribute to the development of internal working models about the world. During periods of active abuse, alcohol-abusing parents may be inconsistent, insensitive, angry, and rejecting (MacPherson et al, 2001;Tweed & Ruff, 1996). The inconsistent behavior displayed by some alcohol-abusing parents may convey to their children that they are unworthy.…”
Section: Discussionmentioning
confidence: 99%
“…Many descriptions of alcoholic families include these characteristics at this disturbed end of the continuum: poor boundaries, lack of shared emotional focus, tyrannical control, chaos, and unresolved conflict. (Beavers, 1981;Tweed & Ryff, 1996).…”
Section: Theoretical Context and Literature Reviewmentioning
confidence: 99%
“…During periods of intense use, the alcohol-misusing parent may be emotionally and physically unavailable to their children (Eiden, Edwards, and Leonard, 2002;Tweed and Ryff, 1996). Non-substance-user parents may be preoccupied by their partner's addiction and may have difficulty maintaining an emotionally supportive home (e.g., Miller, Smyth, and Mudar, 1999).…”
mentioning
confidence: 99%